PERLINDUNGAN HUKUM NASABAH PIALANG BERJANGKA DITINJAU DARI PRAKTIK TRANSAKSI PERDAGANGAN DI INDONESIA - Yohanes Sabbat Satriyawan; Ariy Khaerudin; Suparwi Suparwi (Verstek, 2025)
The type of research used in this study is normative juridical legal research. This study analyzes the protection of futures broker  customers in trading transactions in Indonesia. The purpose of the study is to determine and analyze the legal relationship between customers and futures brokers in futures trading transactions in Indonesia and to determine and analyze legal protection  for  futures  broker  customers  in  transactions  in  Indonesia.  The  method  used  is normative analysis with reference to legal texts and related literature.